2015
DOI: 10.2116/analsci.31.1055
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified and Turn-on Fluorescence Chemosensor Based on Coumarin Derivative for Detection of Aluminium(III) Ion in Pure Aqueous Solution

Abstract: First, 7-hydroxy-4-methylcoumarin (5.00 g, 0.0284 mol) and hexamine (10.0 g, 0.071 mol) in acetic acid (37 mL) were stirred for 5.5 h at 95 C. Then, hydrochloric acid (75 mL, HCl: H2O = 84:100, v/v) was added and further College of Chemistry and Chemical Engineering, Southeast University, Nanjing, Jiangsu 211189, P. R. ChinaA novel chemosensor L based on coumarin Schiff-base was synthesized and investigated. Sensor L showed remarkable selectivity for Al 3+ in Tris-HCl aqueous buffer solution (pH 7.2), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Nine coumarin derivatives 135 – 143 (Figure ) have been reported as chemosensors for aluminum ions (Al 3+ ) and recognize Al 3+ with fluorescence turn-on response as a result of restricted molecular motion upon complexation, as well as the inhibition of a PET effect.…”
Section: Fluorescent Chemosensors Based On Coumarin Platform For Meta...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nine coumarin derivatives 135 – 143 (Figure ) have been reported as chemosensors for aluminum ions (Al 3+ ) and recognize Al 3+ with fluorescence turn-on response as a result of restricted molecular motion upon complexation, as well as the inhibition of a PET effect.…”
Section: Fluorescent Chemosensors Based On Coumarin Platform For Meta...mentioning
confidence: 99%
“…Yan et al reported an aliphatic imine-type sensor ( 140 ), demonstrating a 21-fold fluorescence enhancement in the presence of Al 3+ in a fully aqueous solution, as a result of the inhibition of a PET effect. The sensor was however not fully selective to Al 3+ as Zn 2+ elicited a very similar fluorescent response.…”
Section: Fluorescent Chemosensors Based On Coumarin Platform For Meta...mentioning
confidence: 99%
“…Following the line, the same group developed yet another aluminium sensor 11 based on the coumarin- l -serine hybrid moiety. 58 The amine part of the Schiff base was sensibly chosen to enhance the water solubility and to provide coordination sites. As Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For a complex with 1:1 (H:G) stoichiometry ratio, the association constant with non-linear relationship could be determined by titration curves (Fig. 3) of Benesi-Hilderbrand method [9] according to the eqn 1 [10,11] for UV-visible titration and eqn 2 [12,13] for fluorescent titrations data.…”
Section: Resultsmentioning
confidence: 99%